433 The Knowledge of Sexual Transmitted Diseases Adolescence in Low Economic Level. (October 2012) - Taşar, MA; Demir, H; Bilge, Y Dallar
Abstract : The purpose of this work is to do a research on the level of awareness about sexually transmitted diseases (STD) of adolescence and the factors effecting it. Method: A number of adolescent at the ages of 14–17 (n=527) were asked to complete a survey questioning their level of knowledge of STDs and their sociological and demographical issues. Data were entered into the SPSS 15.0 program and evaluated. A value of p<0.05 was assumed for statistical significance. Findings: 78.9% of the adolescent responded positively to the question of whether or not they are aware of the fact that diseases could be transmitted via sexual intercourse. 48.6% of the adolescent responded negatively to whether or not they knew "how the diseases are transmitted", 59.4% responded negatively to whether or not they know "how to protect themselves from those diseases", and 67.2% responded negatively to whether or not they know "the symptoms of STDs". The count of the right answers were in increase in correlation with the education and economic level of the parents (p<0.05). The results showed that 49.3% of them learned information about STDs at school and from medical institutions. 9.3% of them stated that they had intercourse in the last one-year period and 8.0% of them utilized a method of protection. Result: Awareness level of adults about STDs is inadequate. For that, schools and medical institutions, where they are inclined most to get education, should organize mass education events for them about these matters.